Impact of land slope, tree density and basal area on fire intensity in pinus merkusii plantation forest - Muh. Ihsan; Putu Supadma Putra; Nasri Nasri; Andi Siady Hamzah; Risma illa Maulany; Putu Oka Ngakan (Jurnal Penelitian Kehutanan Wallacea, 2023)
Forest fires are not solely determined by the quantity and quality of plant debris as fuel, but also influenced by some extrinsic factors. This study aims to examine the effect of some factors (slopes, tree density, and tree basal area) on the intensity of forest fires. The study was conducted in a 1 ha (100m x 100m) plot in the Pinus merkusii plantation 10 months after the fire. The plot was divided into 10 m x 10 m subplots, therefore there were 100 subplots. Each tree over 5 cm in diameter found in the plot was numbered consecutively, recorded its species name, measured its diameter, and determined whether it was alive or dead. The slope level in each subplot was measured. Multiple regression analysis was used to detect the influence of slope level, tree density, and basal area on the number of dead trees in each subplot. Results show that slopes, tree density, and basal area influenced proportionally the intensity of forest fires (R2 = 0,507; p<0.05). However, when the partial analysis was applied to detect the influence of each class factor, not all of the classes were found significant. These results reveal that there are several other factors not measured in this study that also influence fire intensity, which we suspect are tapping holes and tree diameter.